2021
DOI: 10.3390/brainsci11111526
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Expectation and Beliefs on the Effects of Non-Invasive Brain Stimulation

Abstract: Non-invasive brain stimulation (NIBS) techniques are used in clinical and cognitive neuroscience to induce a mild magnetic or electric field in the brain to modulate behavior and cortical activation. Despite the great body of literature demonstrating promising results, unexpected or even paradoxical outcomes are sometimes observed. This might be due either to technical and methodological issues (e.g., stimulation parameters, stimulated brain area), or to participants’ expectations and beliefs before and during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 139 publications
(159 reference statements)
0
22
0
Order By: Relevance
“…Thirdly, while blinding efficacy was assessed and achieved in the parent study following the completion of the entire intervention (i.e., 10 stimulation sessions) (Manor et al, 2018), participants' beliefs in the type of stimulation received was not queried after the first stimulation session. Therefore, it is undetermined whether expectancy beliefs influenced the findings in the current results (Braga et al, 2021). Future studies should assess blinding efficacy after each stimulation visit in which outcome measures are taken.…”
Section: Discussionmentioning
confidence: 86%
“…Thirdly, while blinding efficacy was assessed and achieved in the parent study following the completion of the entire intervention (i.e., 10 stimulation sessions) (Manor et al, 2018), participants' beliefs in the type of stimulation received was not queried after the first stimulation session. Therefore, it is undetermined whether expectancy beliefs influenced the findings in the current results (Braga et al, 2021). Future studies should assess blinding efficacy after each stimulation visit in which outcome measures are taken.…”
Section: Discussionmentioning
confidence: 86%
“…Rabipour et al [ 38 , 59 ] demonstrated that participants in tDCS studies have variable assumptions and knowledge about the intervention before the experiment—some participants see tDCS as a promising intervention, while others can be skeptical. The relevance of participants’ expectations for tDCS effects has recently been tackled in a narrative review by Braga et al [ 36 ], who argued for a systematic evaluation of participants’ expectations in NIBS research to control their potential confounding effect.…”
Section: Discussionmentioning
confidence: 99%
“…In tDCS experiments on cognition, if the participants are aware of the received stimulation type, they can engage more (during real stimulation) or less (during sham stimulation) while completing cognitive tasks. On the other hand, expectations may influence the outcomes if participants anticipate the improvement of their performance because of the assumed tDCS benefit [ 36 ]. Moreover, the interaction between awareness and expectations may further influence the results of tDCS experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Instructional manipulations combined with sham tES could induce cognitive placebo or even nocebo effects in healthy individuals ( Turi et al, 2018 ). Ineffective blinding may not only interfere with attentional processes during tES, but might lead to psychobiological responses through expectations ( Colagiuri et al, 2011 , Oken et al, 2008 , Braga et al, 2021 ). Experimentally manipulating the expectancy of tES outcome, e.g., by placebo-inducing written instructions combined with sham tES can on itself influence cognitive functions in young healthy adults ( Turi et al, 2017 , Turi et al, 2018 ).…”
Section: Neuroenhancement and The Placebo Effectmentioning
confidence: 99%